Assessing paediatric safeguarding in rural Australian health services - Enzor, Lesley; Van Bockxmeer, John; Makate, Marshall (Wiley-Blackwell, 2022)
Aim: Establish the incidence, burden and characteristics of paediatric safeguarding concerns in rural Australian ED practice. Methods: Retrospective cohort study of burns, injury and poisoning presentations across 16 months involving 1472 paediatric cases.